A Study of Bone Marrow Aspiration and Biopsy in Adult Patients Presenting with Leukoerythroblastic Blood Picture - V, Shubha H; C, Nirmala; Biligi, Dayananda S (Annals of Pathology and Laboratory Medicine, 2018)
Introduction: The presence of leukoerythroblastosis serves as a valuable clue to the presence of some underlying serious disease. Various infiltrating & non-infiltrating conditions present as leukoerythroblastic picture ranging from infections, sepsis, haemorrhage, haemolysis, anemias to leukemias, lymphomas & metastases. Aims and objectives: To confirm the diagnosis of various conditions presenting with leukoerythroblastosis by studying the bone marrow morphology and to study the distribution of various conditions presenting with leukoerythroblastosis in different age groups and sex. Materials and methods: A total of 50 adult patients presenting with leukoerythroblastosis were studied during the period from October 2014 to August 2016. The bone marrow aspiration and biopsy were preceded by the evaluation of patient’s medical history, clinical and hematological findings with peripheral smear examination for the presence of leukoeythroblastosis. The findings were documented on a proforma. Results: 13 (26%) cases were in the age group of 21-30 years which constituted the largest group. 26 (52%) were males and 24 (48%) were females. The spectrum of conditions presenting with leukoerythroblastosis were non–infiltrating conditions with one (2%) normal study, 8 (16%) erythroid hyperplasias, 21 (42%) megaloblastic anemias, 5 (10%) myelodysplastic syndromes and 1 (2%) hypoplastic marrow and among the infiltrating conditions were 2 (4%) acute myeloid leukemias, 6 (12%) myeloproliferative disorders, 1 (2%) metastatic deposit, 2 (4%) lymphoproliferative disorders and 3 (6%) multiple myelomas. Conclusion: Leukoerythroblastosis indicates the extent to which bone marrow reacts to stress and disease. It is characteristic & diagnostic of a disordered marrow function. Thus, bone marrow aspiration and biopsy help in establishing an early diagnosis and better prognosis of the disease can be expected.